The Influence of Reading Text Activities on Students’ English Speaking Ability at SMA Islam Al Fanisa Raas: English - Mislawiyadi Mislawiyadi; Ukhtul Iffah; Sirrul Bari (JOEY: Journal of English Ibrahimy, 2026)
This Research investigated the influence of reading text activities on students’ English speaking ability at SMA Islam Al Fanisa Raas. A quantitative approach with a pre-experimental one-group pre-test and post-test design was employed. The participants consisted of 22 senior high school students. Data were collected through speaking tests administered before and after the implementation of reading text activities. The collected data were analyzed using descriptive statistics and a paired sample t-test. The results revealed a significant improvement in students’ speaking performance after the treatment. The mean pre-test score was 61.36, while the mean post-test score increased to 74.18, indicating a mean gain of 12.82 points. Individual gain scores ranged from 13 to 15 points, demonstrating consistent improvement across all participants. The paired sample t-test confirmed that the difference between pre-test and post-test scores was statistically significant at the 0.05 level, indicating that the observed improvement was attributable to the implementation of reading text activities. These findings suggest that reading text activities provide effective linguistic input and support students in developing speaking ability by enhancing vocabulary use, idea organization, and oral confidence. Therefore, integrating reading-based activities into speaking instruction is recommended as an effective strategy for improving students’ English speaking ability in EFL senior high school contexts.